2011
DOI: 10.1203/pdr.0b013e3182294735
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Electrocerebral Activity and Cerebral Fractional Tissue Oxygen Extraction in Preterm Infants

Abstract: Impaired cerebral oxygen delivery may cause cerebral damage in preterm infants. At lower levels of cerebral perfusion and oxygen concentration, electrocerebral activity is disturbed. The balance between cerebral oxygen delivery and oxygen use can be measured by near-infrared spectroscopy (NIRS), and electrocerebral activity can be measured by amplitude-integrated EEG (aEEG). Our aim was to determine the relationship between regional cerebral tissue oxygen saturation (r c SO 2 ), fractional tissue oxygen extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…Several investigators argue that a lack of normative data [30,31], and similar lack of uniformity in rSO 2 averaging techniques, with monitoring epochs ranging from 5 to 120 minutes across various studies [5,8,10,13,16,17,20,32], currently hinder the use of NIRS as a standard monitoring tool in VLBW neonates. Given the results of our analysis, we recommend 5-15 minutes as a preferred data averaging interval for RrSO 2 and SrSO 2 measurements in order to establish a baseline signal for eventual clinical trend monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators argue that a lack of normative data [30,31], and similar lack of uniformity in rSO 2 averaging techniques, with monitoring epochs ranging from 5 to 120 minutes across various studies [5,8,10,13,16,17,20,32], currently hinder the use of NIRS as a standard monitoring tool in VLBW neonates. Given the results of our analysis, we recommend 5-15 minutes as a preferred data averaging interval for RrSO 2 and SrSO 2 measurements in order to establish a baseline signal for eventual clinical trend monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral rSO 2 (CrSO 2 ) is used as an adjunct to amplitude-integrated electroencephalography in gauging injury in asphyxiated newborns [4][5][6]. While some use of short-term rSO 2 trending exists, expanded use of NIRS monitoring in the neonatal intensive care unit (NICU) has been hindered by a paucity of normative data in stable patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 Even though NIRS was previously not thought to contribute to the predictive value of aEEG, our study adds to the evidence that possibly the use of cerebral NIRS has the added clinical advantage of predicting outcome. 12,13,27,[30][31][32][33] Our study has some limitations. We have a small sample size, similar as in other studies.…”
Section: 6mentioning
confidence: 93%
“…This suggested that higher extraction of oxygen is needed to support brain metabolism. Ter Horst et al (6) investigated the relationship between rScO 2 , cFTOE and aEEG measures in 46 preterm infants. aEEG amplitude changed with increasing gestational age while cFTOE and aEEG amplitude also increased with postnatal age.…”
Section: Assessing Brain Oxygenation and Brain Function Using Simultamentioning
confidence: 99%